Implementation of the Project Based Learning (PJBL) to Increase Students Learning Interest and Learning Outcomes in Biotechnology Concept - Nurlaela, Ela; Sutresna, Yoyon; Helina, Nina (Universitas Lampung, 2023)
The success of learning can be influenced by various factors including students learning interests. However, there are still many students who have a low interest in learning, and the interest in learning that is owned by students can affect the learning outcomes of students during the learning process. This study aims to determine the increase in learning interest and student learning outcomes in biotechnology material. The research method used is the class action research method (CAR). The subjects in this study were all students in class IX B of junior high school 1 Baregbeg totalling 35 people with details on 17 boys and 18 girls. The data analysis technique used in quantitative descriptive research allowed the data obtained from the results of the research to be processed with the help of Microsoft Excel 2016 to find out the proportions of student interest in learning, the proportion of interest in learning each cycle, and the proportion of completeness of student learning outcomes on the cognitive aspect. Based on the results of the research it shows that the Project Based Learning (PJBL) model can increase student interest in learning and learning outcomes of students in biotechnology concept with an interest in learning in cycle I obtaining a proportion of 67% and in cycle II of 77%. Then the learning outcomes of students in cycle I were 49% mastery and in cycle II they increased to 91%. So with the proportion that has increased in cycle II the Project Based Learning (PJBL) model is very effective to be applied in the learning process as an effort to increase interest in learning and student learning outcomes in biotechnology concept in class IX. DOI: http://dx.doi.org/10.23960/jbt.v11.i1.27242